Response of Blackgram (Vigna mungo L.) Cultivars for Nipping and Graded Levels of Nitrogen for Higher Productivity under Irrigated Conditions - Subbaiyan Marimuthu; Koilpitchai Nelson Navamaniraj; Muthuselvan Kathiravan; Palaniyappan Balasubramanian; Udayarpillai Surendran; Salah El-Hendawy; Mohamed A. Mattar (Agronomy, 2024)
Blackgram (Vigna mungo L.) holds significant importance among grain legumes, particularly in terms of its production and productivity. Over the years, the decline in the cultivation area of this crop has become increasingly evident due to its persistently low yields. Many technologies are being implemented to improve the yield, and nipping is one of them. The main objective of this paper was to standardize the nipping timing and graded levels of nitrogen (N) application on growth and seed yield in blackgram cultivars under irrigated conditions. A study with three blackgram cultivars (cv.), three levels of N, and three intervals of nipping was taken up during the winter and monsoon seasons of 2018 and 2019, respectively. The study revealed that blackgram cv. VBN8 recorded a higher plant height of 49.52 cm, a higher number of branches (4.08), a higher number of pods per plant (47.75), a higher seed yield of 882 kg.ha−1, and a benefit cost ratio (B:C ratio) of 2.49. Among the graded levels of nutrients, applications of 125% N and 100% phosphorus (P) and potassium (K) recorded the highest growth and yield attributes, with a B:C ratio of 2.33. Nipping at 25 days after sowing (DAS) registered a higher number of branches (4.08), more pods per plant (48.14), and a seed yield of 902 kg.ha−1 with a B:C ratio of 2.36. Higher N, P, and K uptake was observed in blackgram VBN8, with an application of 150% recommended N and 100% P and K and nipping at 25 DAS. To conclude, application of 125% recommended N and 100% P and K and nipping at 25 DAS were found to be significant in enhancing the productivity of blackgram and NPK uptake, and resulted in 14% more profit than no nipping treatments.